2022
DOI: 10.1002/mc.23493
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 plays an oncogenic role in small cell lung cancer

Abstract: Small cell lung cancer (SCLC) is a malignant tumor characterized by aggressiveness and dismal prognosis. The specific role of ubiquitin‐like PHD and RING finger domain (UHRF1), a frequently overexpressed cancer‐promoting gene in various tumors, is poorly understood in SCLC. Herein, we explored the potential carcinogenic role of UHRF1 in SCLC. First, public databases were used to analyze the expression of UHRF1 in SCLC, and tissue specimens in our center were examined to confirm the results while clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…UHRF1 overexpression has been found in various sub-types of lung cancer, and can be used for the precision diagnose of lung cancer [ 78 ]. UHRF1 expression levels are significantly elevated in small cell lung cancer (SCLC) and are closely associated with poor prognosis [ 79 ]. Mechanistically, UHRF1 binds to YAP1 (the major downstream effector protein of the Hippo signaling pathway) and inhibits the ubiquitination-dependent protein degradation, thereby stabilizing YAP1 protein in tumor cells of SCLC (Fig.…”
Section: Uhrf1 Mediates Non-epigenetic Regulationmentioning
confidence: 99%
“…UHRF1 overexpression has been found in various sub-types of lung cancer, and can be used for the precision diagnose of lung cancer [ 78 ]. UHRF1 expression levels are significantly elevated in small cell lung cancer (SCLC) and are closely associated with poor prognosis [ 79 ]. Mechanistically, UHRF1 binds to YAP1 (the major downstream effector protein of the Hippo signaling pathway) and inhibits the ubiquitination-dependent protein degradation, thereby stabilizing YAP1 protein in tumor cells of SCLC (Fig.…”
Section: Uhrf1 Mediates Non-epigenetic Regulationmentioning
confidence: 99%
“…UHRF1 has been identified as a significant promoter of cell proliferation and tumor growth in numerous cancers, including retinoblastoma, osteosarcoma, lung cancer, and breast cancer [ 14 , 18 , 20 , 62 , 65 ]. Specifically, in small cell lung cancer (SCLC), UHRF1 promotes SCLC proliferation through its interaction with the yes-associated protein 1 (YAP1), preventing YAP1 ubiquitination and degradation [ 62 ].…”
Section: Uhrf1 In Cancersmentioning
confidence: 99%
“…UHRF1 has been identified as a significant promoter of cell proliferation and tumor growth in numerous cancers, including retinoblastoma, osteosarcoma, lung cancer, and breast cancer [ 14 , 18 , 20 , 62 , 65 ]. Specifically, in small cell lung cancer (SCLC), UHRF1 promotes SCLC proliferation through its interaction with the yes-associated protein 1 (YAP1), preventing YAP1 ubiquitination and degradation [ 62 ]. In non-small cell lung cancer (NSCLC), the expression of long non-coding RNA UHRF1 Protein-Associated Transcript (UPAT) contributes to UHRF1 overexpression, which leads to an increase in cell proliferation and enhances the transition from the G1 to the S phase of the cell cycle [ 63 ].…”
Section: Uhrf1 In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 UHRF1 regulates various epigenetic markers, including repressive epigenetic markers, such as m5C methylation, as well as active chromatin mark, such as H3K4me3, leading to transcription factor-like activity. 13 Previous study revealed that depletion of UHRF1 promoted apoptosis, 14,15 cell cycle arrest, 14 metastases, 16 epithelial-mesenchymal transition, 17 and acted as an oncogene in multiple cancers, including small cell lung cancer, 18 pancreatic cancer, 19 intrahepatic cholangiocarcinoma 20 and GBC. 14 In this study, we suppose to investigate the clear functions of YTHDF1 and m6A-dependent functions on regulating m6A/UHRF1 axis in gallbladder cancer progression.…”
mentioning
confidence: 99%